KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH PENAWARAN SAHAM PERDANA DI BURSA EFEK INDONESIA - Henny Ritha; Yusi Wahmisa Kurniasari (Jurnal Akuntansi, 2021)
The purpose of this research is to analyze differences in the company's financial performance before and after the initial public offering (IPO) on the Indonesian stock exchange using financial ratios. The research variables consisted of Current Ratio, Debt Equity Ratio, Debt Asset Ratio, Return on Equity, Return on Asset, Net Profit Margin, Fixed Asset Turnover, Turn Asset Turnover. The population in this research were companies that conducted an IPO in 2014 and selected samples based on the purposive sampling method were 14 companies. The method of data analysis uses paired test with the Wilcoxon signed ranked test. The results showed that there were no significant differences on Current Ratio, Return on Asset, Net Profit Margin, Fixed Asset Turnover and Total Asset Turnover before and after the IPO while significant differnces were found on Debt Equity Ratio, Debt Asset Ratio and Return on Equity. Keywords: Financial performance, Financial ratio, IPO. References: Arfandi, A., & Taqwa, S. (2018). Analisis Kinerja Keuangan Sebelum dan Sesudah Initial Public Offering (IPO) Pada Perusahaan Non Keuangan di Bursa Efek Indonesia. Wahana Riset Akuntansi, 6(2), 1347–1364. Brigham, E. F., & Houston, J. F. (2018). Dasar-dasar Manajemen Keuangan. Penerbit: Salemba Empat Cahyani, R. T., & Suhadak, S. (2017). Analisis Kinerja Keuangan Perusahaan Sebelum dan Sesudah Perusahaan Melakukan IPO (Initial Public Offering) Di Bursa Efek Indonesia (BEI) (Studi pada Perusahaan yang Listing Di BEI pada tahun 2013). Jurnal Administrasi Bisnis (JAB). Vol. 1. April 2017 Fitriyani, M.M. (2016). Analisis Kinerja Keuangan Perusahaan Sebelum dan Sesudah Initial Public Offering (IPO) di Bursa Efek Indonesia , Universitas Pendidikan Indonesia. repository.upi.edu | perpustakaan.upi.edu Hartono, J. (2017). Teori Portofolio dan Analisis Investasi. Edisi kesebelas. Yogyakarta: BPFE. Ikhsan, Adhisyahfitri Evalina. (2011). Initial Public Offerings dan Kinerja Keuangan. Jurnal Keuangan dan Bisnis. Vol.3 No. 3. Khatami, N., Hidayat, R. R., & Sulasmiyati, S. (2017). Analisis Kinerja Keuangan Perusahaan Sebelum dan Sesudah Initial Public Offering (IPO) di Bursa Efek Indonesia (Studi pada Perusahaan Non Finansial yang Listing di BEI Tahun 2011). Jurnal Administrasi Bisnis (JAB). Vol. 47. No. 1. Juni 2017. Kusumawati, Fitri Lita dkk. (2014). Analisis Kinerja Keuangan Perusahaan Sebelum dan Sesudah Initial Public Offering (IPO) di Bursa Efek Indonesia (Studi Pada Perusahaan yang Listing di BEI Tahun 2009). Jurnal Administrasi Bisnis (JAB). Vol. 8 No. 2. Maret 2014. Munisi, G. H. (2017). Financial performance of initial public offerings: Companies listed on Dares Salaam Stock Exchange. Banking, Economics and Business Research (ICMABEBR-19). Pastusiak, Radoslaw et al. (2016). Company Profitability Before and After IPO. Is It a Windows Dressing or Equity Dilution Effect?. Prague Economic Papers. Vol. 25. No. 01. Pusporini, Ariyanti. (2014). Dampak Initial Public Offering terhadap Kinerja Keuangan PT Verena Multi Finance Tbk. dan PT Batavia Prosperindo Finance, Tbk. Institut Pertanian Bogor. Putra, E. K., Soesetio, Y., & Wijijayanti, T. (2016). Pengaruh Kinerja Keuangan Perusahaan terhadap Pembentukan Initial Return (Studi pada Perusahaan yang melakukan Initial Public Offering (IPO) di Bursa Efek Indonesia Periode Tahun 2011-2015). Ekonomi Bisnis, 21(2), 179–189. Sugiyono. (2016). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung : Alfabeta. Wirajunayasa, P. A. A., & Putri, I. (2017). Analisis Kinerja Keuangan Perusahaan Sebelum dan Sesudah Initial Public Offerings. E-Jurnal Akuntansi Universitas Udayana, Vol. 19(3), 1916–1942.